Signs of apoptosis in circulating tumor cell subpopulations with phenotypes associated with stemness and epithelial-mesenchymal transition in breast carcinoma - V. M. Perelmuter; E. S. Grigorieva; M. V. Zavyalova; L. A. Tashireva; V. V. Alifanov; O. E. Saveleva; S. V. Vtorushin; E. L. Choynzonov; N. V. Cherdyntsevа (Успехи молекулярной онкологии)
Introduction. Ability of circulating tumor cells (CTC) initiate metastases in distant sites is associated primarily with their resistance to apoptosis which allows them to retain viability in the blood. Knowledge of phenotypical signs associated with this ability would allow to predict the risk of metastases and optimize adjuvant therapy.Aim. To examine signs of apoptosis in CTC populations with various phenotypical characteristics.Materials and methods. The study included 58 patients with invasive breast carcinoma of unspecified type, stages T1–4N0–3M0. Cell concentrates extracted from patients’ whole blood were stained with an antibody cocktail against CK7 / 8, CD45, EpCAM, CD44, CD24, CD133, ALDH, N-cadherin which allowed to identify CTC with signs of stemness and epithelial-mesenchymal transition. Annexin V and 7‑amino-actinomycin D staining was used for evaluation of apoptosis stage in CTC populations.Results. Circulating tumor cells are characterized by heterogeneity in respect to signs of stemness and epithelial-mesenchymal transition and presence of early and late signs of apoptosis and necrosis. CTC phenotypes including co-expression of epithelial marker CK7 / 8 and stemness marker CD133 (but not CD44) are characterized by absence of signs of apoptosis. Co-expression of CK7 / 8 and CD133 in CTC with stemness markers CD44+ / C D24– is associated with development of early but not late signs of apoptosis and necrosis. Circulating tumor cells without co-expression of CK7 / 8 and CD133 could have both early and late signs of apoptosis and necrosis. Circulating tumor cells phenotypes with signs of early apoptosis expressing CD133 remain in blood after non-adjuvant chemotherapy opposed to CTC without CD133 expression.Conclusion. There are CTC phenotypical signs associated with stemness and epithelial-mesenchymal transition and linked to apoptosis resistance or sensitivity.